(3EOGQI GdGLJeGYGJ (B:s (3GdLhGfH GdGLQGFjI (B/s - (3OQI, YHO GdHGQj GHQGgjes ((3YeGf(B: s (3OGQ hGFd(B, s, 2009)
(3GdOjebQGWjI h GdGLQGAGJ GdHQdeGfjI h ebOeI NfQj e(B. (3QhHQJ h bhGYOg GdJfXjejI ddGLJeGYGJ , JMOjO eaghe GdGLJeGYGJ h CfhGYgG , YedjI eYGdLI GdGbJQGMGJ aj GdGLJeGYGJ , bVGjG eNJGQI aj GOGQI GdGLJeGYGJ eY hLhO HYV GdJWHjbGJ aj GOGQI GdGLJeGYGJ (B.s
(3edGMb U(B.101s
Keywords: (3GdGLJeGYGJs; (3GdGOGQIs